Oxidative Stress Measurement in Frozen/Thawed Human Sperm: The Protective Role of an In Vitro Treatment with Myo-Inositol - Rosetta Ponchia; Annunziata Bruno; Asia Renzi; Claudia Landi; Enxhi Shaba; Francesca Paola Luongo; Alesandro Haxhiu; Paolo Giovanni Artini; Alice Luddi; Laura Governini; Paola Piomboni (MDPI AG, 2021)
Despite its widespread use, sperm cryopreservation induces serious detrimental alterations in sperm function; indeed, it is commonly associated with decreased sperm viability and motility, and DNA fragmentation. Mechanisms of human sperm cryodamage are thought to be multifactorial, but oxidative stress seems to have a prominent role. A huge amount of data supported the cryoprotective effect of different antioxidants able to minimize the detrimental effects of reactive oxygen species (ROS) and improve the quality of spermatozoa. Among others, myo-inositol is one of the most powerful and has been reported to be effective in improving sperm quality and motility when used both in vivo and in vitro. This study aimed to determine the in vitro impact of myo-inositol in ameliorating sperm oxidative status during sperm cryopreservation. In particular, we demonstrated a significant improvement of sperm parameters (vitality and motility) when myo-inositol was added after sperm thawing (p < 0.05). Moreover, we showed that myo-inositol induces a significant increase in oxygen consumption, the main index of oxidative phosphorylation efficiency and ATP production. Finally, by means of 2D-electrophoresis, we demonstrated a significant decrease in the level of carbonyl groups, the main structural changes occurring in conditions of oxidative stress (p < 0.05). In conclusion, the sperm cryopreservation procedure we developed, assuring the reduction of ROS-induced sperm modifications, may improve the in vitro procedure currently used in ART laboratory for sperm cryostorage.